Expert System for Diagnosing Metabolic Syndrome at The Tembilahan Regional General Hospital - samsudin, samsudin; ilyas, ilyas; Zulrahmadi, Zulrahmadi; Tanjung, Faizal (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
Metabolic syndrome is a disease that is considered trivial and common in society. When sufferers feel the effects of the disease, it will make treatment and healing difficult. To detect this disease early, an expert system application with the forward chaining method is needed so that this application makes it easier to detect disease early. The method for developing this system uses the waterfall method. System analysis and design using UML. System testing uses a black box where system test results are received. Application user testing, using statistical tests with Beta testing with a 95% confidence level, the system can be accepted and trusted. Based on these results, this system can be a solution for early detection of metabolic syndrome.